Biological determinants perpetuating the transmission dynamics of mosquito-borne flaviviruses - Xugang Wang; Usama Ashraf; Huanchun Chen; Shengbo Cao; Jing Ye (Emerging Microbes and Infections, 2023)
Mosquito-borne flaviviruses present a major public health concern. Their transmission is sustained in a cycle between mosquitoes and vertebrate hosts. However, the dynamicity of the virus-mosquito-host triad has not been completely understood. Herein, we discussed determinants of viral, vertebrate host, and mosquito origins that ensure virus adaptability and transmission in the natural environment. In particular, we provided insights into how proteins and RNAs of flaviviruses, blood parameters and odours of humans, and gut microbiota, saliva, and hormones of mosquitoes coordinate with each other to perpetuate the virus transmission cycle. A better knowledge of mechanisms permitting flaviviruses dissemination in nature can provide opportunities for establishing new virus-controlling strategies and could guide future epidemic and pandemic preparedness.